The elderly mentally ill--whose responsibility?. Issue 6028 (17th July 1976) - Pasker, P; Thomas, J P; Ashley, J S
Abstract : The elderly mentally ill make considerable demands on health and social services. To evaluate the need for these services a one-day census of all people aged 65 and over was carried out in an area containing 220 000 people (40 000 over 65). Data were obtained on the nursing needs and psychiatric state of the 2162 elderly people in hospital or local authority residential homes for the elderly, or living at home receiving care from the community nursing service. One-third were classified as having psychiatric problems, more than half of them being outside hospital. Residential homes and community nurses play a significant part in caring for the elderly mentally ill, and an integrated but flexible manpower policy is important.